Koperasi Syariah : Sarana Pembinaan Alternatif Kesejahteraan Masyarakat Kecamatan Sagulung Batam - Slamet Hasanudin Hasanudin (Jurnal Ilmiah Ekonomi Islam, 2022)
Sharia cooperatives are conversions from conventional cooperatives with an approach that is in accordance with the teachings of Islamic law. Sharia cooperatives are a means for Muslims to run and develop their economy in a sharia manner, where cooperatives are carried out in accordance with their sharia maqashid, so that a just life can be enforced and welfare can be realized properly. This study aims to determine how the role of cooperatives in carrying out guidance in order to realize the welfare of the community according to sharia in Sagulung sub-district, Batam. In conducting this research, the writer uses a qualitative method with a descriptive analysis approach. The data is taken and processed from literacy studies, where the authors read and examine books related to sharia cooperatives, journals on capital management by the banking system, and articles from other Muslim business practitioners, as well as observations and interviews at the Javaraya Sharia Cooperative, Sagulung, Batam. The results of this study indicate that sharia cooperatives are a very practical and efficient forum for fostering the sagulung batam community in realizing their welfare in accordance with sharia. This may also be appropriate if applied to the wider general public.